Effect of different levels of nitrogen and microbial inoculants on yield and quality of cabbage (Brassica oleracea var capitata) cv Pride of India - KUMARI, C; MANKAR, ABHAY; KARUNA, K; SOLANKEY, S S; SINGH, V K (The Indian Journal of Agricultural Sciences, 2015)
The present investigation was carried out at Bihar Agricultural University, Sabour during rabi season of 2010-11 in Factorial Randomized Block Design (RBD) for yield and quality contributing characters. The microbial inoculant (Azospirillum) significantly reduced the number of days taken to head initiation (54.74 days). The plants developed under nitrogen level of 150 kg N/ha along with microbial inoculant Azospirillum significantly produced the highest average head weight (1.653 kg) per plant. The highest head yield (527.09 q/ha) was obtained with the use of microbial inoculant Azospirillum and proved its superiority over Azotobacter. For quality components the lowest moisture content in head (80.00%) was associated with nitrogen level of 200 kg N/ha + Azospirillum. Moreover, the highest dry weight per head (117.62 g) was associated with nitrogen level of 150 kg N/ha. The plants grown at nitrogen level of N0 (0 kg N/ha) produced significantly maximum ascorbic acid in head (86.46 mg/100 g). Therefore, it may be concluded that application of microbial inoculants basically Azospirillum as seedling treatment as well as soil application of nitrogen @ 150 kg/ha was the most effective treatment combination for higher yield and quality in cabbage.